Cr-Si sintered body

A high-strength Cr-Si sintered body with a stoichiometric composition and fine particle size is developed, addressing the low strength and cracking issues of existing Cr-Si sintered bodies, and enabling efficient thin film formation on large substrates.

JP7647978B2Active Publication Date: 2025-03-18TOSOH CORP
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2024082522
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-05-21
Publication Date
2025-03-18
Estimated Expiration
2040-05-26

AI Technical Summary

Technical Problem

Existing Cr-Si sintered bodies used for thin film formation have low strength and are prone to cracking, making them unsuitable as large sputtering targets for semiconductor and solar cell applications.

Method used

A high-strength Cr-Si sintered body is produced using quenched alloy powders with a stoichiometric composition of CrSi2 and Si, characterized by an average particle size of 40 μm or less and a bending strength of 100 MPa or more.

Benefits of technology

The resulting Cr-Si sintered body exhibits high strength and resistance to cracking, enabling the production of high-quality thin films on large substrates with improved productivity and reduced particle generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007647978000001
    Figure 0007647978000001
Patent Text Reader

Abstract

To provide a high strength Cr-Si-based sintered body containing chromium (Cr) and silicon (Si) and not causing a micro-crack in processing and bonding even in a case of a large body.SOLUTION: A Cr-Si-based sintered body contains chromium (Cr) and silicon (Si) and has an area of 180 cm2 or more on one side of the sintered body, an average grain diameter of 40 μm or less, a bending strength of 100 MPa or more, and a density of 95.5% or more.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a large-sized Cr-Si sintered compact for forming a thin film. [Background technology]

[0002] In recent years, silicides such as CrSi2 have been used as thin films in many places such as semiconductors and solar cells due to their characteristics. Sputtering methods are often used industrially to produce thin films. However, compositions containing silicides such as CrSi2 generally have low strength and are prone to cracking during processing of the sputtering target and during discharge during film formation, making them difficult to use as sputtering targets. Therefore, in Patent Document 1, a sputtering target with a Cr and Si crystal phase is produced by a thermal spraying method. However, the thermal spraying method does not provide sufficient strength in areas with a low Cr distribution, and the sputtering target produced by the thermal spraying method using powder of the silicide phase does not have high strength.

[0003] In addition, in Patent Document 2, a composition with a fine eutectic structure is produced by a melting method. However, the proportion of eutectic structure is small in the melting method, and high strength cannot be achieved in a composition with a large amount of primary crystals. Furthermore, when the size is increased, it becomes difficult to control the crystal structure due to differences in cooling speed, and unevenness in strength increases.

[0004] Furthermore, Patent Documents 3 and 4 make no mention of systems containing a large amount of silicide because the silicide phase is brittle.

[0005] In recent years, the size of silicon substrates has increased, and large sputtering targets are now necessary, but when large sputtering targets are manufactured due to their insufficient strength, microcracks occur during processing and bonding, resulting in poor product yields. Furthermore, when a film is formed using a sputtering target containing microcracks, particles caused by the cracks are generated, which also reduces the yield of film products. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2017-82314 A [Patent Document 2] Special Publication No. 2013-502368 [Patent Document 3] JP 2002-173765 A [Patent Document 4] JP 2003-167324 A Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide a large-sized, high-strength Cr-Si sintered body containing Cr (chromium) and silicon (Si). [Means for solving the problem]

[0008] The present inventors conducted extensive research into a manufacturing process for a Cr-Si sintered body having a stoichiometric composition of chromium silicide (CrSi2) and silicon (Si) and containing a specific amount or more of the CrSi2 phase. As a result, they discovered that a high-strength Cr-Si sintered body can be obtained by using a rapidly cooled alloy powder such as a gas atomized powder, and thus completed the present invention.

[0009] That is, the aspects of the present invention are as follows. (1) A Cr-Si sintered body containing chromium (Cr) and silicon (Si), with an area of ​​180 cm 2 The Cr-Si sintered body is characterized in that it has an average grain size of 40 μm or less and a bending strength of 100 MPa or more. (2) The Cr-Si sintered body according to (1), wherein the oxygen content is 1 wt % or less. (3) A Cr-Si sintered body according to (1) or (2), in which the total amount of impurities Mn+Fe+Mg+Ca+Sr+Ba is 200 ppm or less. (4) A sputtering target comprising the Cr-Si sintered body according to any one of (1) to (3). (5) A method for producing a thin film by sputtering using the sputtering target according to (4).

[0010] The present invention will be described in detail below.

[0011] The present invention is a Cr-Si sintered body containing chromium (Cr) and silicon (Si), and the area of ​​the sintered body is 180 cm 2 The Cr-Si sintered body is characterized in that it has an average grain size of 40 μm or less and a bending strength of 100 MPa or more.

[0012] The area of ​​the Cr-Si sintered body of the present invention is 180 cm 2 Preferably, the range is 180 to 3000 cm or more. 2 , and more preferably 700 to 3000 cm 2 , particularly preferably 1000 to 3000 cm 2 It is 180cm 2 For a sintered body smaller than this, the substrate (for example, a Si substrate) used in producing a thin film cannot be of a production-level substrate size, and the productivity of the thin film is poor.

[0013] The Cr-Si sintered body of the present invention is characterized in that its average grain size is 40 μm or less. If the grain size exceeds 40 μm, the strength decreases rapidly. To obtain a stable high strength, the average grain size is preferably 1 to 40 μm, more preferably 1 to 20 μm, and particularly preferably 1 to 10 μm.

[0014] The flexural strength of the Cr-Si sintered body of the present invention is 100 MPa or more, more preferably 100 to 500 MPa, even more preferably 150 to 500 MPa, and particularly preferably 200 to 500 MPa. If the strength of the sintered body is lower than 100 MPa, microcracks are likely to occur during grinding and bonding processes, and the yield is high, resulting in good productivity. Furthermore, even when high power is applied during sputtering, particle problems are unlikely to occur.

[0015] The oxygen content of the Cr-Si sintered body of the present invention is preferably 1 wt% or less, more preferably 0.5 wt% or less, even more preferably 0.1 wt% or less, and even more preferably 0.05 wt% or less, from the viewpoints of particle generation when made into a film and the yield of the film product.

[0016] The Cr-Si sintered body of the present invention has a total impurity content of Mn+Fe+Mg+Ca+Sr+Ba of 200 ppm or less, preferably 100 ppm or less, and particularly preferably 50 ppm or less.

[0017] Of the total impurity amount of Mn+Fe+Mg+Ca+Sr+Ba being 200 ppm or less, the total impurity amount of Fe+Mn is preferably 100 ppm or less, and particularly preferably 50 ppm or less.

[0018] Furthermore, among the total impurity amount of Mn+Fe+Mg+Ca+Sr+Ba being 200 ppm or less, it is preferable that the total impurity amount of Mg+Ca+Sr+Ba is 3 ppm or less, and particularly preferably 2 ppm or less.

[0019] Next, the method for producing the Cr-Si sintered body of the present invention will be described.

[0020] The method for producing the Cr-Si sintered body of the present invention includes steps including (1) an alloy raw material preparation step in which chromium and silicon are used by a gas atomization method, an arc melting method or the like, and (2) a sintering step in which the obtained raw material powder is sintered in a pressure sintering furnace such as a hot press furnace at a pressure of 50 MPa or less and a sintering temperature of 1100°C to 1800°C.

[0021] Hereinafter, each step of the method for producing a Cr-Si sintered body of the present invention will be described.

[0022] (1) Alloy raw material preparation process The raw materials used are chromium and silicon. The purity of the raw materials is preferably 99.9% or more, and more preferably 99.99% or more. If the raw materials contain a large amount of impurities, this can cause abnormal grain growth during the firing process and can be a source of particle generation during film formation. Also, raw materials with a low oxygen content are preferable. If the raw materials contain a large amount of oxygen, the final sputtering target will contain a large amount of oxygen, which can cause particle generation.

[0023] It is preferable to rapidly cool the alloy raw material powder by a method such as gas atomization to produce a powder with a fine structure. In particular, particles produced by the gas atomization method are spherical in shape, measuring several tens of μm, and the powder has a fine crystalline phase within the spheres. Because of the small surface area and fine grains, the sintered body after firing can be low in oxygen and high in strength. A high-strength sintered body can be produced even when fine powders are mixed, but the amount of oxygen is high. Conversely, low oxygen can be produced by mixing coarse grains, but the strength is low. Other methods for producing raw materials include rapid cooling methods such as quenched ribbon and arc melting.

[0024] The conditions for the gas atomization method are preferably melting temperature +50 to 300°C. More preferably, it is +100 to 250°C. Here, the melting temperature refers to the temperature at which the raw material powder melts, and is usually 1300 to 1500°C. If the difference from the melting temperature is small, the crystal phase with the higher melting point of the two phases precipitates first, making it difficult to refine the particles. On the other hand, if the difference from the melting temperature is large, the particles sinter together after atomization and adhere to the wall surface, resulting in a poor powder recovery rate.

[0025] In addition, it is preferable to store the powder after gas atomization in a vacuum or in an inert atmosphere of nitrogen, argon, etc. If the powder is left in the air, oxidation will occur from the surface, and the amount of oxygen in the powder will increase.

[0026] (2) Firing process The powder thus obtained is then preferably sintered in a pressure furnace such as a hot press furnace, since it is difficult to densify the powder in a non-pressure furnace due to the low diffusion coefficient of silicon.

[0027] The hot press pressure during sintering is preferably 50 MPa or less. If the pressure exceeds 50 MPa, it is difficult to prepare a hot press mold capable of applying pressure. When producing a large sintered body, the hot press pressure is preferably 5 to 50 MPa, more preferably 5 to 20 MPa, and particularly preferably 5 to 10 MPa.

[0028] The firing temperature is 1100° C. to 1800° C. If the temperature is less than 1100° C., the density does not increase sufficiently, and if the temperature exceeds 1800° C., the material may melt depending on the pressure of the hot press. The cooling rate is not particularly limited, and can be appropriately determined in consideration of the capacity of the sintering furnace, the size and shape of the sintered body, and the fragility of the sintered body.

[0029] The holding time during firing should be within 1 to 5 hours. If it is shorter than 1 hour, uneven temperatures will occur in the furnace and hot press mold, making it difficult to obtain a uniform structure. Conversely, if the holding time is long, productivity will decrease.

[0030] The atmosphere during firing is not particularly limited, but a vacuum or an inert atmosphere such as argon is preferable.

[0031] The Cr-Si sintered body of the present invention can be ground into a plate shape using a machining machine such as a surface grinder, a cylindrical grinder, a lathe, a cutting machine, or a machining center.

[0032] The Cr-Si sintered body of the present invention can be made into a sputtering target made of the Cr-Si sintered body of the present invention. As a method for producing a sputtering target, the sputtering target can be obtained by bonding to a backing plate or backing tube made of oxygen-free copper, titanium, or the like as necessary using indium solder or the like.

[0033] In addition, a thin film can be produced by sputtering using the resulting sputtering target. Effect of the Invention

[0034] The Cr-Si sintered body of the present invention has a large surface area (180 cm 2 Since these materials have the above properties and are highly strong, when used as sputtering targets, they are less likely to crack during product processing, produce fewer particles even under high output, and can be used to form films on large substrates, making it possible to achieve high productivity. EXAMPLES

[0035] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. The measurements in the examples were carried out as follows. (1) Density of sintered body The relative density of the sintered body was calculated by measuring the bulk density by the Archimedes method in accordance with JIS R 1634 and dividing it by the true density. The true density of the sintered body was calculated by dividing the weight a [g] of crystalline phase A and the weight b [g] of crystalline phase B by their respective true densities Ma [g / cm 3 ], Mb [g / cm 3 ] was used to calculate the arithmetic mean expressed by the following formula. d=(a+b) / ((a / Ma)+(b / Mb)) (2) Average particle size The sintered compacts were polished to a mirror finish, observed under a scanning electron microscope, and the average grain size was measured from the obtained sintered compact structure image by the diameter method. At least three random points were observed, and more than 300 grains were measured. (Scanning electron microscope observation conditions) Accelerating voltage: 10kV (3) Transverse bending strength Measurements were performed in accordance with JIS R 1601. (Measurement conditions for flexural strength) Test method: Three-point bending test Distance between fulcrums: 30mm Sample size: 3×4×40mm Head speed: 0.5mm / min. (4) Analysis of oxygen content After grinding 1 mm or more from the surface of the sintered body after firing, a sample was cut out from any part and the analytical values ​​were used as the measurement data.

[0036] Measurement method: Impulse furnace melting - infrared absorption method Equipment: LECO TC436 Oxygen and Nitrogen Analyzer (5) Analysis of metal impurities After grinding 1 mm or more from the surface of the sintered body after firing, a sample was cut out from any part and the analytical values ​​were used as the measurement data.

[0037] Measurement method: Glow discharge mass spectrometry (GDMS) (6) Film formation method A sintered body having a diameter of 10.16 cm was cut out from an arbitrary position of the sintered body, and In bonding was performed to prepare a sputtering target. (7) Microcracks in the target after coating After the film was formed, the target surface was observed to check for the presence or absence of cracks.

[0038] Measurement method: Optical microscope Example 1 Cr flakes (4N): 18wt% and Si flakes (5N): 82t% were melted in a carbon crucible, and powder was produced by gas atomization at a melting temperature of 1650°C. The powder was sieved (sieve size: 300μm) in air to adjust the particle size of the powder.

[0039] Next, this powder was placed in a carbon mold (15.2 cmφ) and sintered by a hot press method to obtain a sintered body. (Firing conditions) Firing furnace: Hot press furnace Heating rate: 200℃ / hour Heating atmosphere: vacuum reduced pressure atmosphere Firing temperature: 1275℃ Pressure: 30MPa Baking time: 3 hours A sintered body with a size of 15.2 cmΦ×7 mmt and no microcracks was obtained. The properties of the sintered body are shown in Table 1. The density of the sintered body was measured as follows: Crystal phase A: CrSi2 (true density 4.98 [g / cm 3 ]) is 37 wt%, and crystalline phase B:Si (true density 2.3 [g / cm 3 ]) was calculated as 63 wt%.

[0040] Thereafter, a sputtering target of 10.16 mmφ was used to form a film. (Film formation conditions) Film forming power: 800W Gas pressure: 0.5Pa Gas atmosphere: Ar only Film forming time: 1h After the film was formed, the surface of the target was observed with an optical microscope, and it was confirmed that no cracks were generated.

[0041] Example 2 Except for changing the firing conditions and the size of the sintered body, the sintered body was produced in the same manner as in Example 1. Table 1 shows the characteristics of the sintered body and the presence or absence of microcracks in the target after film formation.

[0042] Example 3 42 wt% Cr flakes (4N) and 58 wt% Si flakes (5N) were melted in a carbon crucible, and powder was produced by gas atomization at a melting temperature of 1650°C. The powder was sieved in air (sieve size: 300 μm) to adjust the particle size. A sintered body was produced in the same manner as in Example 1, except that the firing conditions and sintered body size were changed. The sintered body characteristics and the presence or absence of microcracks in the target after film formation are shown in Table 1. The density of the sintered body was measured using crystal phase A: CrSi2 (true density 4.98 [g / cm 3 ]) is 87 wt%, and crystalline phase B:Si (true density 2.3 [g / cm 3 ]) was calculated as 13 wt%.

[0043] (Examples 4 to 6) Except for changing the firing conditions and the size of the sintered body, the sintered body was produced in the same manner as in Example 1. Table 1 shows the characteristics of the sintered body and the presence or absence of microcracks in the target after film formation.

[0044] Example 7 80 wt% Cr flakes (4N) and 20 wt% Si flakes (5N) were melted in a carbon crucible, and powder was produced by gas atomization at a melting temperature of 1900°C. The powder was sieved in air (sieve size: 300 μm) to adjust the particle size. A sintered body was produced in the same manner as in Example 1, except that the firing conditions and sintered body size were changed. The sintered body characteristics and the presence or absence of microcracks in the target after film formation are shown in Table 1. The density of the sintered body was measured using crystal phase A: Cr3Si (true density 6.46 [g / cm 3 ]) is 48wt%, and crystal phase B: Cr5Si3 (true density 5.87[g / cm 3 ]) was calculated as 52 wt%.

[0045] Example 8 48 wt% Cr flakes (4N) and 52 wt% Si flakes (5N) were melted in a carbon crucible, and powder was produced by gas atomization at a melting temperature of 1700°C. The powder was sieved in air (sieve size: 300 μm) to adjust the particle size. A sintered body was produced in the same manner as in Example 1, except that the firing conditions and sintered body size were changed. The sintered body characteristics and the presence or absence of microcracks in the target after film formation are shown in Table 1. The density of the sintered body was measured using crystal phase A: CrSi2 (true density 4.98 [g / cm 3 ]) was calculated as 100wt%.

[0046] Comparative Example 1 18 wt% Cr powder (4N) and 82 wt% Si powder (5N) were mixed, sintered at 1250°C, and then pulverized. After that, the mixture was placed in an Fe can, degassed under vacuum, the can was welded, and sintered by HIP. The properties of the sintered body are shown in Table 1. Microcracks occurred in the target after film formation. The density of the sintered body was measured and found to be crystalline phase A: CrSi2 (true density 4.98 [g / cm 3 ]) is 37 wt%, and crystalline phase B:Si (true density 2.3 [g / cm 3 ]) was calculated as 63 wt%.

[0047] Comparative Example 2 42 wt% Cr powder (4N) and 58 wt% Si powder (5N) were mixed, sintered at 1250°C, and then crushed. Then, sintered by hot pressing. The properties of the sintered body are shown in Table 1. Microcracks occurred in the target after film formation. The density of the sintered body was measured and found to be crystalline phase A: CrSi2 (true density 4.98 [g / cm 3 ]) is 87 wt%, and crystalline phase B:Si (true density 2.3 [g / cm 3 ]) was calculated as 13 wt%.

[0048] Comparative Example 3 Powder was prepared in the same manner as in Example 3 and sintered by hot pressing. The properties of the sintered body are shown in Table 1. In addition, microcracks were observed in the target after the film was formed. Crystal phase A: CrSi2 (true density 4.98 [g / cm 3 ]) is 87 wt%, and crystalline phase B:Si (true density 2.3 [g / cm 3 ]) was calculated as 13 wt%.

[0049] [Table 1]

Claims

1. It is a Cr-Si sintered body containing chromium (Cr) and silicon (Si), and the area of ​​one side of the sintered body is 180 cm 2 The Cr--Si sintered body is characterized in that it has an average grain size of 40 μm or less, a bending strength of 100 MPa or more, and a density of 95.5% or more.

2. 2. The Cr-Si sintered body according to claim 1, wherein the amount of oxygen is 1 wt % or less.

3. 3. The Cr-Si sintered body according to claim 1, wherein the total amount of impurities Mn+Fe+Mg+Ca+Sr+Ba is 200 ppm or less.

4. A sputtering target comprising the Cr-Si sintered body according to any one of claims 1 to 3.

5. A method for producing a thin film by sputtering using the sputtering target according to claim 4.

Citation Information

Patent Citations

  • Preparation of high tenacity nanocrystalline silicide coating

    CN101481791A

  • Silicon-alloy-containing target material and preparation method thereof

    CN105331939A

  • Sputtering target and its manufacture

    JP1993214523A

  • Sputtering target

    JP2002173765A

  • Metal silicide sputtering target and method for manufacturing the same

    JP2003167324A